An Analysis of Students’ Reading Comprehension Ability of 2022 International Class Students of Geographic Education Department at Universitas Negeri Padang - Sinamo, Frilance; Syafei, An Fauzia Rozani (Universitas Negeri Padang, 2024)
Reading comprehension ability is the crucial and a fundamental skill for academic success. This study aimed to find out the reading comprehension ability and to investigate the factors that contribute to variations of reading comprehension ability of the students of Geography Education Department international class. This research is a descriptive mixed-method research. The data were collected from 28 international class students of Geography education department of Universitas Negeri Padang. The instrument of this research was reading comprehension test which is TOEFL reading test and interview. The result shows that the students have an insufficient reading comprehension ability in reading English text, and there are some factors that contributed to the insufficient of reading comprehension ability of the students such as, home environment, socioeconomic status, prior academic experience and motivation. As the result, the reading comprehension ability were 57% failed, 36% inadequate, and 7% adequate. Furthermore, for the factors that contribute to their reading comprehension ability which are from the total of 28 students, 19 students said that they don’t have supportive home environment in developed reading habits, 11 students said that their socioeconomic status are not appropriate enough, 20 students claimed the lack of prior academic experience and 19 student confess that they are not enjoy reading or less motivation in read. The findings suggest some program that needed to be improve in the international class program of Geography education department to provide more efficient and creative reading activities for the student to developed their reading interest and reading habits.